The Impact of Educator Effectiveness on Student Competitiveness: A Case Study in Cilegon City Junior High Schools - Yusuf , Furtasan Ali; Hayadi , B. Herawan; Budiman, Arif (Journal Corner of Education, Linguistics, and Literature, 2024)
Students' competitiveness can be increased through various ways such as studying effectively, developing social and emotional skills, and participating in extracurricular activities. The emphasis on increasing students' competitiveness is expected to help them to become successful and competent individuals in their future lives. This research aims to examine the influence of teacher performance on student competitiveness in State Junior High Schools (SMPN) in Cilegon City, with achievement motivation, student achievement and student absorption as intervening variables. The approach used is quantitative with a survey type, collecting data through questionnaires from 546 teachers at State Middle Schools in Cilegon City. The sampling technique was proportional stratified random sampling, with a sample size of 85 based on the Slovin formula with an error rate of 10%. Data analysis was carried out using inferential statistics using the Statistical Package for the Social Sciences (SPSS) version 26 approach. The results of the research show that teacher performance (X) from the results of the multiple linear regression test can be seen that the t-count (t-stat) value for the teacher performance variable is 5.165, where this value is greater than the t table, namely 1.66412 with a significance level of 0.05 (α = 5%) and degree of freedom (df) = 80. These results indicate that directly the teacher performance variable has a significant influence on competitiveness (Z) of 0.442. Meanwhile, the statistical test value on the Sobel test is 2,428 and the p-value or Sig value. is 0.015, where the p-value is smaller than the significance level of 0.05 (α= 5%), so it can be concluded that the variable absorption capacity (Y3) is significantly able to mediate the teacher performance variable (X) on competitiveness (Z). The conclusion of this research is that teacher performance directly has a significant influence on student competitiveness, and teacher performance has an influence on competitiveness with absorptive capacity as an intervening variable.